HUBUNGAN ANTARA KEBIASAAN BELAJAR DENGAN HASIL BELAJAR SISWA KELAS V SD SE-KECAMATAN TAMPAN - Saputra, Alfredo; Noviana, Eddy; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:Based on observations of researcher in class VC SDN 105 Pekanbarufound study habits students that less well , study habits less well will affect learningoutcomes. The purpose of this research is to find a significant relationship betweenstudy habits with learning outcomes students class V SD se-Kecamatan Tampan. Thisresearch was conducted at 8 elementary schools with sample 301 students. Theinstrument used for the study habits using questionnair that have been tested validityand reliability and documentation for learning outcomes.Data analysis using SPSSversion 20. The results recearch obtain study habits above average as much as 164students and students with study habits under average as much as 137 students, whilelearning outcomes above average as much as 160 students and students with learningoutcomes under average as much as 141 students.Data on study habits and learningoutcomes normal distribution with significant level 0,20 and 0,06. On indicatorrelationships delay avoidance with learning outcomes r obtainable as big as 0,40,while on indicator relationships work method with learning outcomes r obtainable asbig as 0,38. For relationships between study habits with learning outcomes r obtainableas big as 0,45 with moderate relationships level. Study habits influence 20% towardlearning outcomes. There is a significant relationship between study habits withlearning outcomes students class V SD se-Kecamatan Tampan where t hitung (8,61) >tabel (1,65).Keywords: study habits, learning outcomes